Development Of Integrative Microbial Fuel Cell- Fermentative For Bioelectricity Production From Food Waste - Nur Saidatul Nisa Shakila, Jafree (2022)
Food waste (FW) production is expanding in accordance with population increase and worldwide economic expansion. Therefore, the present works deal to designed of laboratory scale double chamber microbial fuel cell (MFCs) to generate the energy from the organic waste. The experiment was carried out to create bioelectricity from kitchen waste of cafeteria at University Malaysia Pahang (UMP) as a substrate for MFC. The device was operated under anaerobic condition at anode and aerobic conditions at cathode side at time duration of 7 days evaluations. The experimental reading was recorded at an interval of 5 hours. The performance of bioelectricity generation was compared between two difference type dilution which is 70% and 40% for Treated FW and Raw FW were evaluated in MFC. The maximum average voltage generation of Treated 70% and 40% were 180.225 mV and 79.46 mV, for the Raw 70% and 40% were 161.200mV and 102.775mV. The graph that obtained observed the increasing maximum average voltage generated on day 1 to day 2 and decline in trend was evaluated on 3 days onwards but have little significant changes in increase trend. From the t-test result shows that p value of each sample is less than α=0.05, it has strong evidence for fail to accept the null hypothesis and concluded that to accept the alternatives hypothesis and vice versa. Based on the result, the comparison Raw FW and Treated FW at 70% and 40% is not same in generating the voltage, while compared between Treated and Raw FW at 70% shows to accept the null hypothesis that means the production of voltage between 2 samples same and no have a significant change. It concludes that no need to treat the FW and can be used directly in the MFCs. As a conclusion of this research, it has been established that MFCs may be utilized to generate electrical energy from FW while emitting less pollution into the environment.